Cobalt-salen intercalated montmorillonite catalyst for air oxidation of p-cresol under mild conditions - Rode, Chandrashekhar V.; Kshirsagar, Vikas S.; Nadgeri, Jayprakash M.; Patil, Kashinath R. (Industrial & Engineering Chemistry Research, 2007)
Air oxidation of p-cresol under very mild conditions (338 K and ambient pressure) was carried out in a semibatch reactor over a solid catalyst developed by intercalating cobalt-salen into the montmorillonite clay. The intercalation of cobalt - salen was done by a simple protocol, and the characterization of the intercalated catalyst was done by XPS, FTIR, and XRD techniques. A total selectivity >= 90% to the oxidation products could be achieved with this solid catalyst by eliminating the undesired coupling side products in air oxidation of p-cresol under ambient pressure conditions. Effect of various process parameters on the conversion and selectivity pattern were also studied, and it was found that the selectivity ratio of aldehyde to alcohol could be varied by suitably changing the reaction conditions. This heterogeneous catalyst was found to give a 5-fold higher turnover number than the homogeneous cobalt - salen complex.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Confinement of nano CdS in designated glass: a novel functionality of quantum dot-glass nanosystems in solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Apte, Sanjay K.; Sonawane, Ravindra S.; Naik, Sonali D.; Patil, Kashinath R. (Journal of Materials Chemistry, 2007)
The present work is the investigation of our novel approach to designing quantum dot-glass nanosystems by confining nano CdS in designated glass and the first employment of such a quantum dot system in solar hydrogen production. The CdS quantum dots were grown in a special glass matrix, which involved a sequence of steps. The obtained glass was of uniformly bright yellow in color and the bulk glass was pulverized to a fine powder of micron size particles. The glass powder was characterized structurally and morphologically. X-Ray diffraction and electron diffraction patterns reveal a hexagonal crystallite system for the CdS quantum dots. Field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray fluorescence spectroscopy and chemical leaching with HCl studies demonstrate that the 2.5 nm size CdS quantum dots distribute homogeneously in a monodispersed form in the glass domain and on the surface with a ``partially embedded exposure'' configuration. This disposition imparts an excellent photostability against photocorrosion and also a facile catalytic function. Therefore, even a very small amount of CdS quantum dots (0.005 g per gram of glass powder) is able to photodecompose H2S under visible light (lambda >= 420 nm) both in alkaline and pure aqueous media and produce solar hydrogen with markedly high quantum yields of 17.5 and 11.4%, respectively at 470 nm. Salient features like reusability after simple washing, corrosionless-stability and remarkable catalytic activity of this quantum dot-glass nanosystem are brought forth by our novel catalyst design and are much acclaimed in large scale solar H-2 production.

Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction